Volcanically forced Madden–Julian oscillation triggers the immediate onset of El Niño - Hyemi Kim; Seung-Ki Min; Daehyun Kim; Daniele Visioni (Nature Communications)
Abstract A process-level understanding of the volcanically forced climate response is an urgent challenge due to its similarities to the potential effects of geoengineering techniques. Although the influence of volcanic forcing on El Niño events has been studied extensively, the mechanisms driving the volcanically-induced immediate onset of El Niño remain uncertain, with many climate models producing a delayed El Niño response compared to observations. In this study, using large ensemble simulations that allow us to isolate the impacts of volcanic forcing on the El Niño response, we demonstrate a mechanism that highlights the central triggering role of the Madden–Julian oscillation (MJO), which has been overlooked in existing literature. Because the land areas surrounding the Indo-Pacific warm pool dry more quickly after a volcanic eruption, the background moisture distribution becomes more favorable for the MJO to propagate eastward from the Indian Ocean into the Pacific. This increases the likelihood of ensemble members having stronger MJO activity in the western Pacific by about 35% compared to non-volcanic years, which subsequently increases the frequency of westerly wind bursts by about 76%, ultimately enhancing the probability of the onset of an El Niño by about 98% following major volcanic eruptions.